Evaluation and impact of descriptive metadata on academic event management in Ukraine: A quantitative study - Auhunas, Sabina (Iberoamerican Journal of Science Measurement and Communication, 2024)
Objective. The study aims to understand the impact of descriptive metadata in academic events. It focuses on the need for analytical frameworks that consider the events' characteristics and the interests of the participants. Design/Methodology/Approach. The article focuses on academic event management and metadata quality based on user preferences and feedback. It surveyed Ukrainian organizers and scholars between August and October 2022, analyzing the responses of 1,270 participants using descriptive statistics and qualitative analysis in RStudio. Results/Discussion. The survey showed that most (over 84%) of organizers and academics are dissatisfied with the metadata quality, with a third rating it as very bad. Frequent errors in metadata emphasized the need for better management, including a preference for using identifiers like ORCID and DOI and a preference for open access to information about academic events. Conclusions. The results highlight the importance of developing specialized tools for metadata management and standardization of metadata elements in Ukraine to facilitate organization and participation in academic events at national and international levels. Originality/Value. The study makes an important contribution to understanding descriptive metadata management in academic events in Ukraine, suggesting ways to improve efficiency in this area.